Theoretical uncertainties in tests of the Cosmological Principle - Guandalin, Caroline (Cadernos de Astronomia, 2024)
Recent studies have found discrepancies in our peculiar speed, derived from our motion relative to the cosmic microwave background and the distribution of matter on large scales. This challenges the Cosmological Principle, a fundamental concept that suggests that our speed should remain consistent in both the cosmic microwave background and the frames of reference of matter. This work explores the luminosity function of quasars, which describes how these objects are distributed in terms of distance and brightness. I will discuss how different models for the luminosity function of quasars impact theoretical estimates of the kinematic dipole and how ignoring the change in quasar brightness over time can lead to different results for our peculiar velocity.
Keywords: Cosmology; quasars; peculiar velocity